Estudo teórico do espalhamento de elétrons pelos radicais livres OH e NH - Lozano, Norka Beatriz Huamán (Universidade Federal de São Carlos, 2003)
Recently, interest on studies of electron scattering by highly-reactive free radicals has grown mostly because their participation on many important processes in several fields such astrophysics, biological and earth s atmospheric studies, as well as in industrial applications. In this work, we report a theoretical study on electron collisions on two radicals, OH and NH. More specifically, calculated elastic differential, integral and momentum-transfer cross sections as well as total (elastic + inelastic) and total absorption cross sections in a wide incident energy range are reported. The main motivation of the present work is to fill partially the existent lacuna in the literatura for electron-radical interactions, since both theoretical and experimental data for such interactions are rare. It is also known that the experimental determination of electron-radical scattering cross sections are very difficult due to the high reactivity of these species. The present work covers incident energies in the (0.5-500.0)-eV range. A complex optical potential is used to describe the dynamics of electron-radical interaction whereas a combination of the Schwinger variational iterative method and the distorted-wave approximation is used to solve the Lippmann-Schwinger scattering equation. Our calculated results are compared with a few theoretical and experimental data for total ionization cross sections, available in the literature for these radicals. Comparison is also made with the results obtained from electron scattering by the molecules H2O e NH3, which are formed by the same chemical elements of the radicals. Several interesting points are observed in the comparison.
Theoretical study about the scattering of electrons by free radicals OH and NH
Keywords: Físico-química; Radicais livres; Espalhamento de elétrons; Colisões elétron-molécula; NAO CATEGORIZADO